4
$\begingroup$

Just began the study of complex analysis. Let $$ f(x,y) = x^2 - y^2 + 2 i xy - x - iy. $$ I need to determine if this function is analytic. This means I have to show the partials satisfy the Cauchy-Riemann equations, and that the partials are continuous. So in this case we have $u(x,y) = x^2 - y^2 - x$ and $v(x,y) = 2xy - y$. Now \begin{align*} \frac{\partial v}{\partial y} = 2x - 1 = \frac{\partial u}{\partial x} \end{align*} and \begin{align*} - \frac{\partial u}{\partial y} = - (-2y) = 2 y = \frac{\partial v}{\partial x} \end{align*} Hence the Cauchy-Riemann equations are satisfied, which is a necessary condition for being analytic, but not sufficient. Now I have to show the partials are continuous? How do I do that?

$\endgroup$
  • $\begingroup$ Get out your epsilons and deltas, in the usual way? $\endgroup$ – Chappers Sep 26 '15 at 15:19
  • 2
    $\begingroup$ In a complex analysis course it's safe to assume you can just say that the partials are continuous because they are polynomials. $\endgroup$ – Git Gud Sep 26 '15 at 15:20
  • $\begingroup$ No need to show that the partial derivatives are continuous. CR + continuity of $f$ is enough. $\endgroup$ – A.Γ. Sep 26 '15 at 17:26
4
$\begingroup$

Let $g$ define by $g(z)=z^2-z$. $g$ is clearly analytic on $\mathbb C$. You have that $f(x,y)=g(z(x,y))$ which is a composition of two analytic function.

| cite | improve this answer | |
$\endgroup$
2
$\begingroup$

We have that $u = u(x,y)$ and $v=v(x,y)$ are polynomial functions of $x$ and $y$. If you know that polynomials are continuous functions and that derivatives of polynomials are again polinomials, you're done.

| cite | improve this answer | |
$\endgroup$
0
$\begingroup$

Another way is to transform your function into a function of $$z^{-}$$, where z^ is the conjugate of z, i.e., if: $$z= x+iy , z^{-}=x -iy$$:

$$x= \frac {z+z^{-}}{2} $$ $$y= \frac { z -z^{-}}{2i}$$

and the resulting function should be a function of $z$ exclusively. The simplest example likely is : $$f(z)= x+iy $$ Then : $$f(z)= \frac {z+z^{-}}{2}+ i\frac{z-z^{-}}{2i}= \frac {z+z^{-}}{2}+ \frac{z-z^{-}}{2}=z$$

| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.